Penegakan Hukum Terhadap Tindak Pidana Pertambangan Batu Cinnabar Ilegal - Hakim, Dandy Alvian; Sopacua, Margie Gladies; Muammar, Muammar (PATTIMURA Law Study Review, 2025)
Luhu Village, West Seram Regency has a Cinabar Stone Mine. In addition to the people of Luhu Village, many people from outside the area also come to seek a living at the location. On the one hand, the community is very grateful because the results of the mining activities are very noticeable for improving the family economy, so that many of the needs of families and school children can be met. However, on the other hand, the mining activities they carry out do not have a permit from the government and are illegal activities. Law No. 4 of 2009 has regulated in detail the mining procedures, where the perpetrators, both individuals and legal entities who carry out mining activities without a permit, are declared illegal miners. The research method used in this study is Normative Empirical. The data needed was obtained, both from the West Seram Police, and from the community around the mining area. From the data collected, after being analyzed, it can be concluded that 1) Legal handling of illegal mining crimes in Luhu Village is carried out in three stages of handling; a) Socialization is carried out to the community, b) Preventive measures are taken, and c) Repressive measures are taken against perpetrators who are still stubborn; 2) In carrying out law enforcement, there are obstacles, both related to geographical factors, minimal personnel and supporting equipment, limited economic conditions of the community and cultural factors.